Implementing a recommender system for CS undergraduate students using machine learning - Tasnuva, Umama Sumlin; Aumi, Azmanul Abedin; Shishir, Shariful Islam (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.